Enhancing MSME Capacity in Barru Regency: Government Policies and Development of Competitive Products - Pratiwi, Dian (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal